Socialism! Theoretical Organ of The Workers Party of Jamaica - Munroe, Trevor; Levy, Horace; Dimov, Yuri; Burchett, Wilfred; DeSouza, Irene (My University, 1979)
Perspectives on the Socialism! : theoretical organ of the Workers Party of Jamaica in 1979
60 pgs. Typescript, sepia-toned, fragile.
Keywords: Black people - Jamaica - Politics and government.; Black people - Jamaica - History; Marcus Garvey - 1887-1940; Minimum wage - Jamaica; Eight-hour movement - Jamaica; Land reform - Jamaica - History; Workers Party of Jamaica.; Jamaica Politics and government 1962-; Political parties - Jamaica.; Politics and government.; Jamaica - Social conditions - Serials.; Jamaica - Economic conditions - Serials.; Garvey, Marcus, 1887-1940.